Strategies to Increase Teacher Innovativeness through Strengthening Learning Organisation, Creativity, Self-Efficacy and Job Satisfaction - Chatarina Febriyanti; Henny Suharyati; Widodo Sunaryo (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
The rapid evolution of the educational landscape and the growing demand for adaptability underscore the need for teachers to continuously develop innovative capabilities as part of their sustainable professional growth. This study aims to identify optimal strategies, methods, and solutions for enhancing teacher innovativeness. Employing a quantitative research approach grounded in established theoretical frameworks, the study was conducted over a two-year period. The sample consisted of 121 civil servant teachers from 12 public elementary schools across six districts in Depok City. The findings reveal that five direct influence hypotheses were supported, while two were not. In contrast, all hypotheses related to indirect influences were accepted. The results suggest that fostering a learning organization and increasing job satisfaction are key strategies for enhancing teacher innovativeness. Implementation should focus on strengthening weak indicators within each variable and prioritizing interventions based on their strategic importance. This study contributes to the body of knowledge by offering actionable insights for developing innovative teaching practices through targeted, evidence-based strategies and solutions. Keywords: Teacher Innovativeness, Learning Organization, Creativity, Self-Efficacy, Job Satisfaction.